Populist Parties as Agents of Democratic Change: Comparing Uganda and South Africa - Sithole, Neo (POLARITIES, 2026)
The following paper investigates the dual capacity of populist parties to function as either forces of institutionalization or pluralization in democratic trajectories by looking at two opposing cases: the National Resistance Movement (NRM) in Uganda and the Economic Freedom Fighters (EFF) in South Africa. The comparative logic of this paper is grounded in the different designs of the party systems, Uganda and South Africa represent divergent regime types (hybrid authoritarian vs liberal democracy), but share histories of liberation struggle and dominant party systems. This temporal and systemic variation provides analytic leverage to examine populism’s contextual effects. The primary conclusion is that populism’s impact on African democracy is an arguably progressive one in so far as party systems are concerned. Although it had long-term authoritarian inclinations, the NRM’s early populism in Uganda steered the institutionalization of political participation and oversaw the transition toward multi-party politics. On the other hand, despite using illiberal rhetoric, the EFF in South Africa has promoted pluralization and broader representational inclusion while operating within established democratic standards. The study comes to the conclusion that, depending on their setting, chronology, and relationship to institutions, populist parties in Africa can act as both challengers and correctives to dominant party systems.